Swamp Thing. Book one, Wild things - Veitch, Rick; Veitch, Rick (DC Comics, 2024)
"Classic Swamp Thing stories written and drawn by legendary comics creator Rick Veitch return to print for the first time in years! Rick Veitch originally joined DC's seminal Swamp Thing series as an artist during writer Alan Moore's game-changing run, bringing to life some of the most inventive horror and fantasy concepts ever seen in mainstream comics. Following Moore's departure, Veitch took over as both writer and artist, continuing the revered creative legacy of Swamp Thing, and adding elements of time travel and metaphysics to one of the most unique comics of its era"--